PEMODELAN KEBISINGAN LALU LINTAS BERDASARKAN VOLUME LALU LINTAS MENGGUNAKAN MULTIPLE LINEAR REGRESSION PADA JALAN KEDUNG COWEK SURABAYA - Firra Rosariawari; Muhammad Almadhany (EnviroUS, 2021)
Kedung Cowek road is a primary arterial road serving a national scale, so it has a high traffic volume that causes traffic noise. So it is necessary to have a traffic noise model that can predict traffic noise to facilitate efforts to control traffic noise. This study aims to obtain a traffic noise model based on the traffic volume of each type of vehicle. The method used in this research is a direct survey on Kedung Cowek road to obtain data on noise levels and traffic volume. Data analysis to obtain traffic noise modeling using Multiple Linear Regression with the help of Minitab software version 19. The traffic noise model on Kedung Cowek road obtained is LEQ = 71.292 + 0.001811 MC + 0.00487 LV - 0.0078 HV with a value the coefficient of determination (R2) of 0.5940. This model is still not very good, because many vehicles use non-standard exhausts which cause higher noise levels.